Caracterização tribológica das lâminas de corte de trituradores utilizados no processo de tratamento de resíduos sólido - Souza, Willian Martins (2023)
In Brazil, changes in production processes are observed due to environmental and social factors, which have as their biggest consequence the increase in the generation of solid waste. Because of these changes, it is essential to improve the efficiency of solid waste treatment processes, Thus, this work seeks to compare in laboratory tests the wear resistance of the cutting blades used in a solid waste crusher in the city of Aparecida de Goiânia, after application of different materials that can be used in the manufacture of the component, since the main problem presented was the loss in productivity in the treatment of waste due to wear of components of the crusher. After collecting a sample of cutting blade was identified through the study of Scanning Electron Microscopy (SEM) with Secondary Electrons (SE) and Backscattered Electrons (ERE), and also with Energy Dispersive Spectroscopy (EDS) that the type of wear preponderant in the tribological pair is the abrasive. From this premise, the laboratory experiment chosen was the rubber wheel wear test, because it is the method that best fits the system wear mechanisms, the same validated according to ASTM G-65. For the rubber wheel wear test were performed using samples of SAE 1060 steel and SAE 410 stainless steel heat treated. The studies demonstrated that it is not feasible to change the material used in the manufacture of the component, since the wear rates of the SAE 410D stainless steel samples were 55% higher than that of the samples that reproduce the condition of the cutting blade. This analysis is not limited only to one field, and can be extended to other sectors, using tribology as a reference, seeking to contribute to the academic production of production engineering, improving solid waste treatment operations.